Rethinking Rufus : Sexual Violations of Enslaved Men - Foster, Thomas A. (Book collections on Project MUSE., 2019)
"This book uses a wide range of sources on slavery--early American newspapers, court records, slave owners' journals, abolitionist literature, and the testimony of former slaves collected in autobiographies and in interviews--to argue that enslaved black men were sexually assaulted by both white men and white women. Scholarship has focused on women's exploitation and abuse and has noted that many of our sources similarly emphasize the abuse of women, silencing the stories of men. However, a careful reading of extant sources finds that sexual assault of enslaved men took a wide variety of forms, including outright physical penetrative assault, forced reproduction, sexual coercion and manipulation, and psychic abuse."--Provided by publisher